FORENSIC ANALYSIS VIDEO METADATA AUTHENTICITY DETECTION USING EXIFTOOL - Suhardjono, Suhardjono; Popon Handayani ,; Hari Sugiarto,; Nurul Aisyah,; Arman Syah Putra, (Journal of Innovation Research and Knowledge, 2022)
The background of this research is how to detect the authenticity of a video using exit which will be able to determine which video is original and which video is fake. With this forensic analysis, the previous data will be opened and will provide clarity to data seekers. The method used in this study is to use the Exiftool method, by comparing 2 MP4 format videos by turning off the 2 videos, it will be known which video is original and which video has been changed. The problem in this study is how to prove that the video is the original video and has not been converted into another format or there has been a change in color and others, therefore this research will prove through the forensic data contained in the video. The purpose of this study is to prove that there are changes that exist in a video by comparing the two videos, the version has not been changed and the version after it has been changed. With this comparison, it can be proven that something has happened to the video based on existing forensic data.